Optimistic Sentiment of Investors and Its Impact on the Dynamics of Iran's Stock Market: "A Comparative Study of the JCPOA Period and the US Withdrawal" - Eyshi Ravandi, Mohsen; Moeinaddin, Mahmoud; Taftiyan, Akram; Rostami Bashmani, Majid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Contrary to classical theory, which considers investors as rational decision-makers, behavioral finance theory assumes that individuals' behavior is not entirely rational and that there is a possibility of irrational behavior in decision-making, with a special emphasis on cognitive and emotional biases. The purpose of this study is to investigate the optimistic sentiment of investors and its impact on the dynamics of Iran's stock market.Methodology:  The research method is applied in terms of purpose and descriptive-post-event in terms of methodology. The statistical population of the study includes all companies listed on the Tehran Stock Exchange during the years 2016-2022 (during the two periods of the JCPOA and the US withdrawal from the JCPOA). The sample size was determined using the systematic elimination method, which resulted in 136 companies. In this study, panel data and dynamic least squares methods were used for data analysis. Additionally, the Arms Index was used to measure investor sentiment, and the two indices of bid-ask spread and market depth were used to measure stock market dynamics.Findings:  The results showed that optimistic sentiments have a significant and inverse impact on the bid-ask spread and market depth.Conclusion: The results showed that investor optimism significantly impacts the bid-ask spread and market depth during the JCPOA and the US withdrawal from the JCPOA.